Collaorative learning techniques to improve english grammatical competence among students of ninth year “c” of basic education, afternoon session at unidad educativa Marieta de Veintimilla, in the city of Loja during the 2018-2019 school year. - Viñamagua Loarte, Andrea Elizabeth (2019)
The main objective of this research work was to improve English grammatical competence among students of ninth year “C” of basic education, afternoon session at Unidad Educativa Marieta de Veintimilla, in the city of Loja during the 2018- 2019 school year. Different methods such as: the scientific, the descriptive, the statistical, and the synthetic-analytical methods were adopted to gather, describe, process, analyze and interpret the obtained results. Likewise, tests and questionnaires were applied to thirty-one participants to diagnose students’ knowledge and to identify their perception about English grammatical competence and collaborative learning techniques. Furthermore, observation sheets and field notes were useful to record students’ progress and their attitude towards the techniques applied. Students improved their learning outcomes significantly in five grammatical aspects: subject-verb agreement, word order, interrogative questions, declarative sentences and parts of speech. In conclusion, collaborative learning techniques were effective to assist students in conveying clear ideas and giving opinions.